CircSNCA downregulation by pramipexole treatment mediates cell apoptosis and autophagy in Parkinson's disease by targeting miR-7 - Sang, Qiuling; Liu, Xiaoyang; Wang, Libo; Qi, Ling; Sun, Wenping; Wang, Weiyao; Sun, Yajuan; Zhang, Haina (Aging (Albany, NY.), 2018)
We aimed to explore the mechanism of pramipexole (PPX) actions in the treatment of Parkinson's disease (PD). Genes related to PD and PPX were screened through bioinformatics retrieval. The PD model was constructed by applying 1-methyl-4-phenylpyridinium (MMP+). The RNA expression levels of circSNCA, , apoptosis-related genes ( , , , and ) and miR-7 were detected by qRT-PCR. Protein expression was determined by western blot. The interactions between circSNCA-miR-7- were verified by dual luciferase assay and immunofluorescence localization. Cell viability was determined by MTT assay. and circSNCA expression levels in PD were downregulated after PPX treatment, consistent with the levels of pro-apoptotic genes. CircSNCA increased expression by downregulating miR-7 in PD as a competitive endogenous RNA (ceRNA). Lower circSNCA expression was associated with the reduced expression of pro-apoptotic ( , , and ) proteins. CircSNCA downregulation could decrease apoptosis and induce autophagy in PD. In conclusion, the downregulation of circSNCA by PPX treatment reduced cell apoptosis and promoted cell autophagy in PD via a mechanism that served as a miR-7 sponge to upregulate .